EFISIENSI SISTEM TATANIAGA ROTAN DI KALIMANTAN TIMUR - Satria Astana (Jurnal Penelitian Hasil Hutan, 1991)
The efficiencv of  rattan marketing  system  in East Kalimantan.  Two criteria were develoaed and used to analyse The first criterium is that the marketing  system is assumed  to be efficient  when  its marketing margin is less than 50% of  the consumer price. Secondly. eventhough the  marketing margin is under 50%, the marketing system is assumed  to be ineffcient   when the profit  margin of the system tends to accumulate in one trader or more.                The results of the study reveal that the rattan marketing system in East Kalimantan is in -efficient. As it is shown, based on the price spread analyses. by the marketing margin of the system that is 66.67%.  This high margin is due to the water content. cost  which accounts for 81.25%   and 62.52%  of  the marketing cost .for  intermediate and inter islanders tarders, respectively. Meanwhile. the  profit margin of the system tends to accumulate in one trader, that is the inter island trader. In fact, the inter. islands trader gains the profit of 12,01%. Markering cost ii only 21.32% of the consumer price. On the other hand, the intermediate trader who spends the marketing cost as  much as 24. 62% of the consumer price gains the profit of  8. 72% only.The accumulation of profit  margin on the inter islands trader would imply.  that in the case of the market  price in-creases or  the marketing cost decreases, profit margin could not be distributed among other operators within marketing channels. including the rattan  farmers.  As a result.  farmers may decrease their production. This may further  Comaound the reduction of domestic rattan trade caused. by the rattan export banpplicies. Therefore,, without  better distribution of profit .margin  among operators within marketing system,  the shortage of rattan supply in the domestic  market  may  not be avoided.